EVALUATION OF PHYTOTOXIC AND CYTOGENOTOXIC POTENTIALS OF LEAF AQUEOUS EXTRACT OF AMPELOCISSUS LATIFOLIA (ROXB.) PLANCH. IN RELATION TO ITS TOTAL POLYPHENOL CONTENT - ANWESA CHAUDHURI,; SANJIB RAY, (International Journal of Pharma and Bio Sciences, 2014)
Ampelocissus latifolia (Roxb.) Planch. is very commonly used in traditional medicine to treat a variety of pathological conditions. The present study aims to explore phytotoxic and cytogenotoxic potentials of leaf aqueous extract of A. latifolia (LAEAL). Phytotoxic activity of LAEAL was investigated by analysing wheat (Triticum aestivum) root morphological changes and fluorescence patterns of ethidium bromide and acridine orange. Tannic acid was used as positive control for fluorescence microscopic analysis. Cytogenotoxic effects of LAEAL were analysed using light and fluorescence microscope on onion (Allium cepa) root tip cells. Germinating wheat seeds treated with LAEAL at concentrations 0.5, 2, and 4 mg/mL for 96 h showed root growth retardation respectively as 51, 59 and 80%. Data indicate that LAEAL treated roots were swelled and the number of root hairs reduced in 48 h as compared to untreated controls. 24 h aged onion roots were treated with LAEAL (0.5 and 2 mg/mL), root tips were fixed at 2- 24 h and different cytogenotoxic effects were analysed from the squashed root tip cells. LAEAL induced dose dependent decrease in mitotic index (p<0.001) and increased frequencies of different types of chromosomal and cytological changes that may be due to the presence of high percentage (21.03±0.9%, tannic acid equivalent) of polyphenols. This study reveals that the leaf aqueous extract of A. latifolia exerts significant phytotoxic and cytogenotoxic effects and therefore this plant should be used in traditional practice with caution.